Human Surfactant Protein D Binds Spike Protein and Acts as an Entry Inhibitor of SARS-CoV-2 Pseudotyped Viral Particles - Hsieh, Miao-Hsi; Beirag, Nazar; Murugaiah, Valarmathy; Chou, Yu-Chi; Kuo, Wen-Shuo; Kao, Hui-Fang; Madan, Taruna; Kishore, Uday; Wang, Jiu-Yao (Frontiers in Immunology, 2021)
Human SP-D is a potent innate immune molecule whose presence at pulmonary mucosal surfaces allows immune surveillance role against pulmonary pathogens. Higher levels of serum SP-D have been reported in patients with severe acute respiratory syndrome coronavirus-1 (SARS-CoV). Studies have suggested the ability of human SP-D to recognise spike glycoprotein of SARS-CoV; its interaction with HCoV-229E strain leads to viral inhibition in human bronchial epithelial (16HBE) cells. Previous studies have reported that a recombinant fragment of human SP-D (rfhSP-D) composed of 8 Gly-X-Y repeats, neck and CRD region, can act against a range of viral pathogens including influenza A Virus and Respiratory Syncytial Virus in vitro, in vivo and ex vivo models. In this context, this study was aimed at examining the likely protective role of rfhSP-D against SARS-CoV-2 infection. rfhSP-D showed a dose-responsive binding to S1 spike protein of SARS-CoV-2 and its receptor binding domain. Importantly, rfhSP-D inhibited interaction of S1 protein with the HEK293T cells overexpressing Angiotensin Converting Enzyme 2. The protective role of rfhSP-D against SARS-CoV-2 infection as an entry inhibitor was further validated by the use of pseudotyped lentiviral particles expressing SARS-CoV-2 S1 protein; ~0.5 RLU fold reduction in viral entry was seen following rfhSP-D treatment (10 µg/ml). The results highlight the therapeutic potential of rfhSP-D in SARS-CoV-2 infection and merits pre-clinical studies in murine models.